Practice of Murabahah and Rahn Contracts in Gold Installment Financing through the BYOND Application at BSI KCP Manukan - Sahrul Ni'am; Muhammad Syauqi (Universitas Hamzanwadi, 2026)
The development of Islamic banking digitalization has encouraged the emergence of application-based financing services, one of which is gold installment financing through the BYOND by BSI application. This product uses a murabahah contract as the sale and purchase agreement and a rahn contract as collateral for financing. This study aims to analyze the implementation of murabahah and rahn contracts in gold installment financing through the BYOND BSI application at BSI KCP Manukan and their compliance with sharia principles and the DSN-MUI fatwa. The study used a qualitative method with a descriptive approach through interviews, observation, and documentation. The results show that the practice of gold installment financing through the BYOND BSI application is in accordance with sharia principles, both in pricing, profit margins, and the use of gold as collateral for financing. In addition to providing easy access to services, the digital system at BYOND BSI still applies the principles of transparency and certainty of contracts in sharia transactions.